PELATIHAN DIGITAL MARKETING UMKM DAN FOCUS GROUP DISCUSSION MULTI-STAKEHOLDER DIWILAYAH PERBATASAN JAGOI BABANG - Beni Novri; Erva Suriyanti; Budi Winanto; Nurmalasari (Indonesian Community Service Journal of Computer Science, 2025)
AbstractThe Community Service (PKM) conducted in Jagoi Babang, Bengkayang Regency aims to provide digital marketing training for MSME craftsmen of rattan in Jagoi Babang and to hold a focus group discussion to build collaboration with multiple stakeholders in the Indonesian-Malaysian border area. This program involves training on creating Instagram accounts for product marketing, product photography techniques, and collaborative discussions with key stakeholders including the Head of PLBN Jagoi Babang, Customs officials, and the Bengkayang Regency Government. The strategic location of Jagoi Babang as a border area offers broader market expansion opportunities through the facilitation of digital technology and export-import processes. The collaborative approach between academics, government, and MSMEs demonstrates an effective model of empowering the creative industry in border areas.AbstrakPengabdian Kepada Masyarakat (PKM) yang dilaksanakan di Jagoi Babang, Kabupaten Bengkayang bertujuan untuk memberikan pelatihan digital marketing pada UMKM pengrajion rotan di Jagoi Babang dan Focus group discussion membangun kolaborasi bersama multi-stakeholder di kawasan perbatasan Indonesia-Malaysia. Program ini melibatkan pelatihan pembuatan akun Instagram untuk pemasaran produk, teknik fotografi produk, serta diskusi kolaboratif dengan stakeholder kunci meliputi Kepala PLBN Jagoi Babang, pejabat Bea dan Cukai, dan Pemerintah Kabupaten Bengkayang. Lokasi strategis Jagoi Babang sebagai kawasan perbatasan memberikan peluang ekspansi pasar yang lebih luas melalui fasilitasi teknologi digital dan proses ekspor-impor. Pendekatan kolaboratif antara akademisi, pemerintah, dan UMKM ini mendemonstrasikan model efektif pemberdayaan industri kreatif di kawasan perbatasan.